Heterogeneous Bank Lending Responses to Monetary Policy: Empirical Evidence from Russia - Kovtun, Zlata (Economy of Regions, 2017)
The monetary policy affects the regional economy through interest rates and its main parameter the Bank of Russia key rate. But do all the banks in the regions respond uniformly to monetary policy changes? The effects of monetary policy actions can vary across the regions within an economic entity, depending on the regional industrial output, the financial structure, household incomes, lending activity, etc. The analysis of the article aims to determine the monetary policy instruments that influence the development or degradation of the regional banking sector in Russia. This helps to identify the heterogeneous commercial bank responses to changes in conducted monetary policy. In order to assess the effects of macroeconomic shocks and instruments of banking supervision on lending activity, the Ordinary Least Squares estimator and Generalized Least Squares technique were applied. The Taylor rule was used to calculate the desired level of interest rate for the each region and, then, to compare the results with the Central Bank interest rate. The empirical results, described in the context of the regional analysis, demonstrate that Central Bank’s interest rate does not affect the lending activity in most of the regions. Finally, the author summarizes conclusions one can draw from the results and provides recommendations for economic policy makers, based on the results of empirical analysis.